Towards the Semantic Web’s application for preparation of reviews – requirements and architecture for the needsof incentive-based semantic content creation - Abramowicz, Witold; Dzikowski, Jakub; Filipowska, Agata; Kaczmarek, Monika; Łazaruk, Szymon (Wykorzystanie mechanizmów sieci semantycznejdo przygotowania i publikacji recenzji – wymagania i architekturaaplikacji, 2011)
In recent years, various Web-based review systems have provided a valuable service to consumers by allowing them to share their assessments of goods and services. In order to provide recommendations being more accurate and tailored to users’ needs, review systems take advantage of semantic annotations and Semantic Web technologies. However, asusers are not really interested in delivering semantic annotations of content, specific tools incorporating incentives’ mechanisms are needed to transform the syntactic content into the machine understandable one. This paper presents a vision, requirements and architecture ofan application offering enhanced ontology-based description of rated objects, semantic-based user profiling as well as supporting contextual semantic search. This application in comparison to the currently existing applications provides a number of incentives motivating users to participate in the review process. The application is to be available using the mobile channel and the Facebook portal
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 206, s. 11-21
Keywords: Semantic Web; semantic annotation; Linked Open Data; incentives; Web 2.0; sieć semantyczna; semantyczne adnotacje; mechanizmy motywujące